MODEL PENGEMBANGAN KEPROFESIAN BERKELANJUTAN (PKB) BERBASIS SEKOLAH PADA GURU SEKOLAH DASAR (SCHOOL BASED CONTINOUS PROFESSIONAL DEVELOPMENT MODEL FOR PREMARY SCHOOL TEACHERS) - Junaidin Basri; Udin Sa'ud; Asep Suryana (Almarhalah, 2021)
ABSTRACKThe implementation of the Continuous Professional Development (PKB) program in improving the quality of primary school teachers in Garut Regency, West Java Province, Indonesia, has not been effective. The research objectives are: (1) to find out the existing PKB program planning carried out by elementary school teachers. (2) to find out the results and impact of the implementation of the PKB program on elementary school teachers, (3) to find a hypothetical model of PKB activities that is more effective for elementary school teachers. The method used is a qualitative method with a case study approach. Data were obtained through observation, observation, interviews and review of documents with research participants as many as 3 elementary schools representing 3 teacher working groups (KKG). Furthermore, the data were analyzed through transcription, data organization, recognition, coding and triingualization.The results of the study found that the Continuing Professional Development (PKB) program for elementary school teachers had not been effective in terms of planning, implementing, evaluating, organizing, and planning follow-up aspects. The resulting impact is only in the aspect of teacher self-development which has increased, while the teacher research culture is still low. To overcome this gap, the researcher offers a hypothetical model of School-Based Continuous Professional Development (PKB) as an alternative model to support the implementation of the existing KKG (Teacher Working Group)-based PKB.Keywords: Teacher, CPD (Continous Professional Development), School Based